Comparative analysis on the socioeconomic drivers of industrial air-pollutant emissions between Japan and China: Insights for the further-abatement period based on the LMDI method. (10th July 2018) - Chang, Miao; Zheng, Ji; Inoue, Yukiko; Tian, Xin; Chen, Qing; Gan, Tiantian
Abstract: Japan has achieved the decoupling of economic growth from air-pollutant emissions since the rapid decrease in air-pollutant emissions in the 1970s and the further-abatement period. Air-pollutant emissions also decreased in China recently. We analyzed the factors driving the changes in air-pollutant emission, which enabled us to identify each factor's contribution and compare the further-abatement period in Japan with the primary reduction stage in China. This study performed the Logarithmic Mean Divisia Index analysis to decompose the industrial-emission changes (SO2 and NOx ) in Japan and China into the socioeconomic factors that drive these changes. Results showed that changes in these factors, especially energy intensity and economic level, contributed differently to the emission reduction in Japan and China because the two countries differed in emission-reduction periods. The decline in emission coefficient, measured by emissions per unit of energy consumption, was the most important contributor to emission reduction in Japan. The other factors did not exert considerable influence. However, energy intensity decrease in China significantly contributed to emission reduction besides emission coefficient, and economic growth had a substantial negative impact on emission reduction. Differences also appeared in contributions from the industrial and economic structure between the two countries. Some factors may have reached their limitation after the rapid reduction period and thus contributed less significantly in the further-abatement period. A tendency toward a similar condition to Japan was also observed in some factorial contributions in China. From a sectoral perspective, emission change was distributed evenly among sectors in Japan than in China. Based on the comparison between the two countries and the "new normal" that China is experiencing, we provided insights for China for further abating industrial air-pollutant emissions in succeeding years. Highlights: Air-pollutant reduction factors between Japan and China were compared. Japan and China experienced further and primary abatement periods, respectively. Changes in the same factor contributed differently between Japan and China. Changes in the union of energy structure and removal rate were vital in both nations. Impacts of energy-intensity reduction and economic growth were obvious for China.